ANALISIS PENGEMBANGAN ORIENTASI KEWIRAUSAHAAN DALAM MENINGKATKAN KINERJA PEMASARAN PADA UMKM DI KOTA BENGKULU - Herry Novrianda; Aan Shar (Universitas Prof. Dr. Hazairin SH, 2021)
The purpose of this study is to find out how the development of entrepreneurial orientation inimproving marketing performance of MSMEs in Bengkulu City. This research is a surveyresearch with a quantitative approach. The sample in this study was the owners of MSMEs intrade sector in Bengkulu City totaling 100 respondents (MSMEs owners) with the samplingtechnique of judgmental (purposive). Data collection methods used questionnaires /questionnaires, interviews and literature study. The analytical method used in this research isusing the average method (mean) and the frequency distribution table. The results of thisstudy indicate that the development of MSMEs entrepreneurial orientation in Bengkulu Cityhas been carried out well by MSMEs owners in Bengkulu City through innovation activities,proactive orientation and risk taking and has an impact on percentage of customer growth,sales, and profits that continue to increase every year which is a determinants of increasingits marketing performance.